LIFE-HISTORY AND FEEDING HABITS OF THE SPOTTED SEER SCOMBEROMORUS GUTTATUS (BLOCK & SCHNEIDER) - Vijayaraghavan, P (Indian Journal of Fisheries, 2016)
THE available information relating to marine fish eggs and larvae of Madrasis covered by the accounts given by John (1951) and Nair (1952 a •+ b). Inthe present paper, which deals with part of the results of the investigationundertaken by the author at the Zoological Research Laboratory, Universityof Madras, for three years (1950-53), on fish eggs and larvae occurringin Madras plankton, the methods of collection, of hatching of the eggs andof rearing the larvae in general are given, together with observations on thelife-history of Scomberomorus guttdtus vidth its food and feeding habits.Our knowledge of the life history of this fish is confined to Delsman's(1931) description of its eggs and larvae reared up to the third day